Effects of selective neonatal hippocampal lesions on tests of object and spatial recognition memory in monkeys - Heuer, Eric (2011)
Earlier studies in monkeys have reported mild impairment in recognition memory following nonselective neonatal hippocampal lesions (Bachevalier, Beauregard, & Alvarado, 1999; Rehbein, Killiany, & Mahut, 2005). To assess whether the memory impairment could have resulted from damage to cortical areas adjacent to the hippocampus, we tested adult monkeys with neonatal focal hippocampal lesions and sham-operated controls in three recognition tasks: delayed nonmatching-to-sample, object memory span, and spatial memory span. Further, to rule out that normal performance on these tasks may relate to functional sparing following neonatal hippocampal lesions, we tested adult monkeys that had received the same focal hippocampal lesions in adulthood and their controls in the same three memory tasks. Both early and late onset focal hippocampal damage did not alter performance on any of the three tasks, suggesting that damage to cortical areas adjacent to the hippocampus was likely responsible for the recognition impairment reported by the earlier studies. In addition, given that animals with early and late onset hippocampal lesions showed object and spatial recognition impairment when tested in a visual paired comparison task (Zeamer, Meunier, & Bachevalier, Submitted; Zeamer, Heuer & Bachevalier, 2010), the data suggest that not all object and spatial recognition tasks are solved by hippocampal-dependent memory processes. The current data may not only help explain the neural substrate for the partial recognition memory impairment reported in cases of developmental amnesia (Adlam, Malloy, Mishkin, & Vargha-Khadem, 2009), but they are also clinically relevant given that the object and spatial memory tasks used in monkeys are often translated to investigate memory functions in several populations of human infants and children in which dysfunction of the hippocampus is suspected.